Early outcomes of patients with Marfan syndrome and acute aortic type A dissection - Farag, Mina; Büsch, Christopher; Rylski, Bartosz; Pöling, Jochen; Dohle, Daniel S.; Sarvanakis, Konstantinos; Hagl, Christian; Krüger, Tobias; Detter, Christian; Holubec, Tomas; Borger, Michael A.; Böning, Andreas; et al. (The journal of thoracic and cardiovascular surgery, 2023)
Background - Acute aortic Stanford type A dissection remains a frequent and life-limiting event for patients with Marfan syndrome. Outcome results in this high-risk group are limited. - Methods - The German Registry for Acute Aortic Dissection Type A collected the data of 56 centers between July 2006 and June 2015. Of 3385 patients undergoing operations for acute aortic Stanford type A dissection, 117 (3.5%) were diagnosed with Marfan syndrome. We performed a propensity score match comparing patients with Marfan syndrome with patients without Marfan syndrome in a 1:2 fashion. - Results - Patients with Marfan syndrome were significantly younger (42.9 vs 62.2 years; P < .001), predominantly male (76.9% vs 62.9%; P = .002), and less catecholamine dependent (9.4% vs 20.3%; P = .002) compared with the unmatched cohort. They presented with aortic regurgitation (41.6% vs 23.0%; P < .001) and involvement of the supra-aortic vessels (50.4% vs 39.5%; P = .017) more often. Propensity matching revealed 82 patients with Marfan syndrome (21 female) with no significant differences in baseline characteristics compared with patients without Marfan syndrome (n = 159, 36 female; P = .607). Although root preservation was more frequent in patients with Marfan syndrome, procedure types did not differ significantly (18.3% vs 10.7%; P = .256). Aortic arch surgery was performed more frequently in matched patients (87.5% vs 97.8%; P = .014). Thirty-day mortality did not differ between patients with and without Marfan syndrome (19.5% vs 20.1%; P = .910). Multivariate regression showed no influence of Marfan syndrome on 30-day mortality (odds ratio, 0.928; 95% confidence interval, 0.346-2.332; P = .876). - Conclusions - Marfan syndrome does not adversely affect 30-day outcomes after surgical repair for acute aortic Stanford type A dissection compared with a matched cohort. Long-term outcome analysis is needed to account for the influence of further downstream interventions.